Effect of NH4OH Treatment on Plasma‐Assisted InP/Al2O3/SOI Direct Wafer Bonding. Issue 5 (10th January 2018) - Gong, Kewei; Sun, Changzheng; Xiong, Bing; Han, Yanjun; Hao, Zhibiao; Wang, Jian; Wang, Lai; Li, Hongtao
Abstract : The effect of NH4 OH treatment on InP/Al2 O3 /SOI direct wafer bonding is investigated. The atomic force microscope (AFM) and water contact angle (CA) results reveal a decrease in root‐mean‐square (RMS) surface roughness and CA of the NH4 OH‐treated InP wafer. X‐ray photoelectron spectroscopy (XPS) analysis is carried out to ascertain the chemical composition of the bonding surfaces. It is found that NH4 OH treatment followed by plasma activation increases the content of oxides on the surface of InP wafer. Based on these results, it is concluded that NH4 OH treatment helps increase hydrophilicity and contact area of the bonding surface, thus contributing to the success of plasma‐assisted InP/Al2 O3 /SOI wafer bonding. Abstract : The effect of NH4 OH treatment on InP wafer is investigated. The water contact angle (CA) results reveal a decrease in CA of the NH4 OH‐treated InP wafer. Atomic force microscope (AFM) and X‐ray photoelectron spectroscopy (XPS) analysis are also carried out to examine the InP surface. Based on these results, it is concluded that NH4 OH treatment contributes to the success of plasma‐assisted InP/Al2 O3 /SOI wafer bonding.